Co-Working Y Su Incidencia En El Desarrollo Local De Los Emprendedores En La Plaza Santa Martha Del Gad Municipal Del Cantón Santo Domingo, Período 2023-2024 - Almeida Mantuano, Hilda Verónica (2025)
Coworking is a work model that offers simultaneous spaces where entrepreneurs, independent professionals, and companies can develop their activities in a collaborative environment. This study analyzes the impact of coworking spaces on the local development of entrepreneurs in the Santa Martha plaza of the municipal GAD of the Santo Domingo de los Tsáchilas canton, Ecuador, for the period 2023-2024. The introduction contextualizes the importance of coworking spaces, raises the problem, the purpose of the study, and its relevance to local economic development. The main objective of this research project is to analyze the impact of coworking spaces on the local development of entrepreneurs in the Santa Martha commercial plaza of the Santo Domingo de los Tsáchilas canton, Ecuador, for the period 2023-2024. For this purpose, methods such as deductive and inductive, and techniques such as observation, interviews, and surveys, were applied. Among the results obtained, it is evident that coworking has facilitated knowledge exchange, project collaboration, and the expansion of contact networks, positively impacting the development of local businesses. However, challenges were identified, such as a lack of time and networking skills among some users. Finally, recommendations include holding frequent networking events, better allocating space, and creating interest groups to strengthen collaboration among entrepreneurs.